O processo de outsourcing: Implementação de um processo de engarrafamento e embalagem. - Ramos, António (2015)
Outsourcing is a management strategy through which an organization transfers work, responsibilities and decision power to an external source. In the present scenario of global competitiveness, where firms have to react more quickly to changes in markets, outsourcing stands out as a strategy that, if adequately used by the organizations, can leverage the differentiation between one firm and its competitors. The growing use of outsourcing as a management strategy by organizations, results from the maturity reached in their use by organizations and an increase of the offer by service providers. With the increasing use of outsourcing, the complexity and the risk associated have also risen. Understanding the perspective of the customer and of the service provider and the outsourcing processes framework should contribute to a success of the customer / service provider relationship and enhance the benefits and reduce their risks. In this work, there is a contextualization of outsourcing, different methods for managing the outsourcing process from the customer's and the service provider perspective are discussed, and a methodology for managing the outsourcing process from the perspective of the service provider is proposed. The methodological approach used in this work was the case study. The case study discusses an initiative to outsource a process of bottling and packaging in the Port Wine industry. In this study it was concluded that the methodology proposed is suitable for the management of the outsourcing process by the service provider.